Capital Market Cointegration and Selection Buy-Sell Stock - Elizabeth Lucky Maretha; Yusni Warastuti (The Indonesian Journal of Accounting Research, 2019)
Abstract:The problem in this study is whether the Indonesian Capital Market is coupled with the ASEAN Capital Market and East Asia Capital Market. And the interest rate of the US Federal Reserve (Fed Rate) and Central Bank of Indonesia's Interest Rates (BI Rate) against the decision of domestic investors and foreign selling-buying of shares. The research model using EViews-9 for stationary testing (ADF-Test), cointegration (Johansen-Test), and t-test and f-test automatically calculated by EViews-9. The study found their cointegration between Capital Markets in ASEAN (JCI, STI, KLSE, SET, PSE), cointegration in Capital Markets in EAST ASIA (NIKKEI, HSI, KOSPI, SHCOMP, TWSE), and cointegration Interest Rates (The Federal Fund Rate, Bank Indonesia Rate). The results of this study also showed that domestic investors in the Central Bank of Indonesia (BI Rate) are deciding to buy shares with the movement. Meanwhile, local investors in the decision to sell stocks saw the index movement of the KLSE and STI index (ASEAN Capital Markets), as well as the TWSE index (East ASIA Capital Market). Foreign Investors buy stocks to decide on the movement of the US Federal Reserve (the Fed) and the Bank Indonesia interest rate (BI Rate).